2018
DOI: 10.3389/fimmu.2018.01776
|View full text |Cite
|
Sign up to set email alerts
|

S100A4+ Macrophages Are Necessary for Pulmonary Fibrosis by Activating Lung Fibroblasts

Abstract: S100A4, a calcium-binding protein, can promote pulmonary fibrosis via fibroblast activation. Due partly to its various cellular origins, the exact role of S100A4 in the development of lung fibrosis remains elusive. Here, we show that in the bronchoalveolar lavage fluid, numbers of S100A4+ macrophages correlated well with S100A4 protein levels and occurrence of idiopathic pulmonary fibrosis (IPF) in patients. A mouse model of bleomycin-induced pulmonary fibrosis demonstrated S100A4+ macrophages as main source f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 47 publications
8
80
2
Order By: Relevance
“…Physicochemical properties of NPs, especially size and specific surface area, have been reported to affect cell viability. Indeed, nanoscaled particles are known to be significantly more toxic than microscaled particles (Li et al 2018;Zhang et al 2018). Here, in our experimental conditions, we showed that ZnO NPs display the larger primary size and the lower specific area, suggesting that ZnO toxicity in this model could be attributed to other properties such as their solubility, morphology, or presence of Zn.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Physicochemical properties of NPs, especially size and specific surface area, have been reported to affect cell viability. Indeed, nanoscaled particles are known to be significantly more toxic than microscaled particles (Li et al 2018;Zhang et al 2018). Here, in our experimental conditions, we showed that ZnO NPs display the larger primary size and the lower specific area, suggesting that ZnO toxicity in this model could be attributed to other properties such as their solubility, morphology, or presence of Zn.…”
Section: Discussionmentioning
confidence: 51%
“…Slc30a1 (FC + 4) and Wdr45 (FC + 5) also involved in metal homeostasis were also highly upregulated, but only after exposure to ZnO or to ZnFe 2 O 4 , respectively. ZnO specific gene signature further englobed the overexpression of Pla2g16 (FC + 7) a membrane damage sensor; S100a4 (FC + 7) involved in macrophage-induced lung fibrosis (Li et al 2018;Zhang et al 2018); Rps14 (FC + 6), Rps27 (FC + 5), and Mrps15 (FC + 5), three protein synthesis regulators. Besides, ZnO exposure signature was also characterized by a downregulation of Tp53inp (FC − 31); a stress response mediator, Slfn3 (FC − 23), Akap9 (FC − 16), and Rock1 (FC − 24), three cell cycle/cytoskeleton regulators; and Zeb2 (FC − 14), Smarca5 (FC − 6), Smarcad1 (FC − 11), and Med13 (FC − 10), four transcriptional regulators.…”
Section: Zno and Znfe 2 O 4 Nanoparticles Reduced The Viability Of Nrmentioning
confidence: 99%
“…and extrinsic S100a4 + cells is currently unknown; however, the differences in cellular morphology may be indicative of discrete S100a4 populations that originate from different sources and perform divergent functions during healing. For example, it has previously been shown that both fibroblasts and macrophages can express S100a4 (22,23). Further investigation to assess the presence of S100a4 + macrophages during tendon healing is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…While the intracellular functions of S100a4 are not well-characterized, the extracellular signaling functions of S100a4 include regulation of multiple cellular processes important in fibrosis including motility (37, 38), differentiation (3941) and survival (39). S100a4 protein levels are strongly correlated with idiopathic pulmonary fibrosis(34), and S100a4 has been suggested as a potential fibrotic biomarker in the liver (4). Consistent with this, we see highest S100a4 expression immediately prior to the period of peak scar formation during tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we see highest S100a4 expression immediately prior to the period of peak scar formation during tendon healing. The therapeutic potential of targeting S100a4 has been well established in the lung, with decreased fibrotic progression following treatment with an S100a4 neutralizing antibody (34), and pharmacological inhibition of S100a4 (42). Moreover, Tomcik et al , demonstrated that deletion of S100a4 prevented bleomycin-induced skin fibrosis(26).…”
Section: Discussionmentioning
confidence: 99%